The Paradox of Mineral Downstreaming: An Economic Analysis of Mining Regulatory Disharmony in Indonesia - Pohan, Choirul Rohmiyanti; Sugiarto, Laga; Hidayat, Arif; Martitah, Martitah (CV. Social Politic Genius (SIGn), 2025)
Although Indonesia’s mineral downstreaming policy aims to enhance value added, its implementation is impeded by fundamental regulatory disharmony. This study aims to evaluate the legal framework of the downstreaming policy to identify inconsistencies and to examine its substantive provisions from an EAL perspective. Employing an interdisciplinary legal research method, this study applies a RIA framework to analyze secondary data comprising statutory instruments and relevant literature. The findings reveal that the policy’s legal framework, while vertically coherent, suffers from severe horizontal disharmony with environmental and spatial planning laws. This disharmony is proven to create significant economic inefficiencies, negative externalities, and high-cost legal uncertainty. The study concludes that active regulatory intervention is a necessity. Therefore, a multi-track strategy is recommended: first, the issuance of precise implementing regulations as a short-term solution; second, the parallel strengthening of non-regulatory interventions; and third, a long-term legislative harmonization agenda.